Method for Receiving Weak Microwave Photonics Signals Based on Electro-Optical Up-Conversion - Qunsong He; Zijing Zhang; Jiaheng Xie; Zhiqiang Shen; Yuan Zhao (IEEE Photonics Journal, 2020)
A novel method for receiving weak microwave photonics signals based on a micro-ring resonator is proposed. This approach uses the nonlinear interaction of a microwave and an optical pump to generate an up-conversion signal to achieve the signal reception. The minimum detectable power of this method reaches −89.79 dBm, which is suitable for the detection of weak signals. The power conversion efficiency and bandwidth have a 10 times promotion compared to similar conversion methods at room temperature. The result also demonstrates that the detection sensitivity can be improved by five orders of magnitude compared to the traditional modulators, and the output signal-to-noise ratio can be improved by more than 17 dB using a micro-ring resonator.